Development of a reliable, sensitive, and convenient assay for the discovery of new eIF5A hypusination inhibitors - Oumayma Benaceur; Paula Ferreira Montenegro; Michel Kahi; Fabien Fontaine-Vive; Nathalie M. Mazure; Mohamed Mehiri; Frederic Bost; Pascal Peraldi (PLoS ONE, 2025)
eIF5A is a translation factor dysregulated in several pathologies such as cancer and diabetes. eIF5A activity depends upon its hypusination, a unique post-translational modification catalyzed by two enzymes: DHPS and DOHH. Only a few molecules able to inhibit hypusination have been described, and none are used for the treatment of patients. The scarcity of new inhibitors is probably due to the challenge of measuring DHPS and DOHH activities. Here, we describe the Hyp’Assay, a convenient cell-free assay to monitor eIF5A hypusination. Hypusination is performed in 96-well plates using recombinant human eIF5A, DHPS, and DOHH and is revealed by an antibody against hypusinated eIF5A. Pharmacological values obtained with the Hyp’Assay, such as the EC50 of DHPS for spermidine or the IC50 of GC7 for DHPS, were similar to published data, supporting the reliability of the Hyp’Assay. As a proof of concept, we synthesized four new GC7 analogs and showed, using the Hyp’Assay, that these derivatives inhibit hypusination. In summary, we present the Hyp’Assay; a reliable and sensitive assay for new hypusination inhibitors. This assay could be of interest to researchers wanting an easier way to study hypusination, and also a valuable tool for large-scale screening of chemical libraries for new hypusination inhibitors.